2017
DOI: 10.22452/mjlis.vol22no2.3
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of vanished URLs: Comparing the efficiency of Internet Archive and Google

Abstract: This article examines the vanishing nature of URLs and recovery of vanished URLs through Internet

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Their study revealed that a total of 2,477 URLs (23.81%) were cited in 406 research articles, containing a total of 10,400 citations, out of which 1,275 URLs (51.47%) were accessible, whereas 1,202 URLs (49.53%) were inaccessible, 500 error being the prominent error code associated with the missing Web citations. Kumar and Kumar (2017) investigated the accessibility of URLs of citations in the articles in the DESIDOC Journal of Library and Information Technology during 2006–2015. A total of 2,133 URL citations were identified out of which 823 (38.58%) were not accessible and HTTP-404 was the most common error associated with the missing URLs (643, 78.13%).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their study revealed that a total of 2,477 URLs (23.81%) were cited in 406 research articles, containing a total of 10,400 citations, out of which 1,275 URLs (51.47%) were accessible, whereas 1,202 URLs (49.53%) were inaccessible, 500 error being the prominent error code associated with the missing Web citations. Kumar and Kumar (2017) investigated the accessibility of URLs of citations in the articles in the DESIDOC Journal of Library and Information Technology during 2006–2015. A total of 2,133 URL citations were identified out of which 823 (38.58%) were not accessible and HTTP-404 was the most common error associated with the missing URLs (643, 78.13%).…”
Section: Literature Reviewmentioning
confidence: 99%
“…While this study established that, after a three-year period, 50% of URL citations from 31 journals could not be accessed (Germain, 2000), a later work reported that almost 17% of the URL references from all the articles published by PLoS Medicine between 2005-2007 were non-operational (Nagajara et al, 2011). Due to the dynamics of the web, several other studies also found a high proportion of URL citations that were not accessible through the web browsers (Sampath Kumar and Vinay Kumar, 2013;Vinay Kumar and Sampath Kumar, 2017;Manjunatha et al, 2020;Shanthakumari, 2021). As the URL refers to the home address of a journal, any changes in its web architecture will affect the accessibility of a particular publication (Ansorge, 2023).…”
Section: Introductionmentioning
confidence: 99%